Performance of videogrammetric displacement monitoring technique under varying ambient temperature. Issue 16 (December 2019) - Zhou, HF; Lu, LJ; Li, ZY; Ni, YQ
There has been an increasing number of attempts to apply videogrammetric technique to displacement measurement of civil engineering structures. Its potentials in structural health monitoring have also gained more attention. This study carried out an investigation on the effect of temperature variation on the measurement accuracy of videogrammetric technique in an effort to examine its feasibility for structural health monitoring. Long-term indoor videogrammetric measurement tests have been conducted, and the performance of the videogrammetric displacement monitoring technique under ambient temperature conditions has been examined. The results show that temperature variations cause non-negligible errors in measured displacements. In line with the temperature variation, the displacement measurement error also contains not only daily fluctuation pattern but also overall trend. In terms of daily fluctuation pattern, the horizontal measurement error and temperatures of vision measurement system are in satisfactory consistency, while the vertical measurement error does not coincide well with temperatures of vision measurement system. In terms of overall trend, the vertical measurement error is highly correlated with temperatures of vision measurement system, while the horizontal one is almost uncorrelated with temperatures of vision measurement system. As an outcome of the dominance of overall trend in the temperature variation over a long time period, the vertical measurement error and temperatures of vision measurement system conform to a favorable linear relationship, while the horizontal measurement error tends to be constrained in a small range when the temperatures of vision measurement system exceed a certain value.